Implementation of a diagnostic decision aid for people with memory complaints and their general practitioners: a protocol of a before and after pilot trial. Issue 6 (16th June 2021) - Linden, Iris; Wolfs, Claire; Perry, Marieke; Metsemakers, Job; van der Weijden, Trudy; de Vugt, Marjolein; Verhey, Frans R; Handels, Ron; Olde Rikkert, Marcel; Dirksen, Carmen; Ponds, Rudolf W H M
Abstract : Introduction: Researchers, policy-makers and healthcare professionals often stress the importance of an early dementia diagnosis. Empirical evidence, however, is scarce leading to a lack of consensus on the necessity of diagnosing dementia early. We emphasise the need for a 'timely' diagnosis, that is, one that occurs at the right moment for a person with memory complaints and his/her significant other. As the optimal timing differs between individuals, the implementation of shared decision making (SDM), preferably by the general practitioner (GP), as the start of a diagnostic trajectory, could help to determine this timely moment. SDM, however, is rarely practised with respect to dementia diagnoses. Therefore, in the context of the Shared Decision-Making regarding Dementia Diagnosis project, a patient decision aid (PtDA) for 'timely' dementia diagnosis in general practice will be developed. This protocol will describe the planned before and after evaluation of its implementation. Methods and analysis: In a mixed-methods pilot study, we will investigate decision-making processes and experiences regarding a diagnostic trajectory before and after the introduction of a PtDA for people with memory complaints, their significant others and their GPs. The 'before group' will receive diagnostics as usual from their GPs. The 'after group' will use the PtDA. We expect the PtDA to increase the level of SDM and to contribute to a timely and personalised diagnostic trajectory. Data will be collected using semistructured interviews, questionnaires and information retrieved from people with memory complaints' medical records. Ethics and dissemination: This study protocol was approved by the Medical Review Ethics Committee of the Maastricht University Medical Centre. The findings will be published in peer-reviewed international journals and presented at conferences. This study was funded by the public funded Dutch Research Institute for Care and Medical Sciences (ZonMw). Trial registration number: NCT04531956 .